Pharmacokinetics of a Cholesterol-conjugated Aptamer Against the Hepatitis C Virus (HCV) NS5B Protein - Chang Ho Lee; Soo-Han Lee; Ji Hyun Kim; Yook-Hwan Noh; Gyu-Jeong Noh; Seong-Wook Lee (Elsevier, 2015)
Hepatitis C virus (HCV) is the major cause of progressive liver disease such as chronic hepatitis, cirrhosis, and hepatocellular carcinoma. Previously, we reported that a 29 nucleotide-long 2'-F pyrimidine modified RNA aptamer against the HCV nonstructural protein 5B efficiently inhibited HCV replication and suppressed HCV infectious virus particle formation in a cell culture system. In this study, we modified this aptamer through conjugation of cholesterol for in vivo availability. This cholesterol-conjugated aptamer (chol-aptamer) efficiently entered the cell and inhibited HCV RNA replication, without any alteration in gene expression profiling including innate immune response-related genes. Moreover, systemic administration of the chol-aptamer was well tolerated without any abnormalities in mice. To evaluate the pharmacokinetics of the chol-aptamer in vivo, dose proportionality, bioavailability, and pharmacokinetic parameters were evaluated by noncompartmental analyses in normal BALB/c mice. Population analysis was performed using nonlinear mixed effects modeling. Moreover, the pharmacokinetics of two different routes (intravenous, IV, versus intraperitoneal, IP) were compared. Cholesterol conjugation showed dose proportionality, extended the time that the aptamer was in the plasma, and enhanced aptamer exposure to the body. Noticeably, the IV route was more suitable than the IP route due to the chol-aptamer remaining in the plasma for a longer period of time.